ON THE QUESTION OF THE CONTINUITY OF THE PHONOLOGICAL THEORY OF ANCIENT INDIA (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-62-69The article deals with the problem of continuity of the fundamental linguistic principles of Ancient India in the formation of the theoretical basis for the development of British phonology. The study provides a comprehensive description of some philosophical views of Indian linguists, which significantly influenced the origin of Indian linguistics and subsequently played an important role in the creation of English phonological theory.Key words: elementary semantic unit, shiksha, Rigveda-pratishakhya, Vajasaneipratishakhya, discretization of speech flow, varna